Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/1059712314528009
|View full text |Cite
|
Sign up to set email alerts
|

Cue-based aggregation with a mobile robot swarm: a novel fuzzy-based method

Abstract: Aggregation in swarm robotics is referred to as the gathering of spatially distributed robots into a single aggregate. Aggregation can be classified as cue-based or self-organized. In cue-based aggregation, there is a cue in the environment that points to the aggregation area, whereas in self-organized aggregation no cue is present. In this paper, we proposed a novel fuzzy-based method for cue-based aggregation based on the state-of-the-art BEECLUST algorithm. In particular, we proposed three different methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…It moves at the same speed in an arena with a size of about 1 m 2 . Moreover, the BEECLUST aggregation using other types of cues [19,20] showed various aggregation times compared to the recorded results in this section. Thus, BEECLUST aggregation relies significantly on the experiment's configuration.…”
Section: Swarm Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…It moves at the same speed in an arena with a size of about 1 m 2 . Moreover, the BEECLUST aggregation using other types of cues [19,20] showed various aggregation times compared to the recorded results in this section. Thus, BEECLUST aggregation relies significantly on the experiment's configuration.…”
Section: Swarm Scenariomentioning
confidence: 99%
“…In addition, we previously implemented BEECLUST using a sound source as the cue for the aggregation [19,20].…”
Section: Swarm Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the proposed strategies outperform BEECLUST method. Fuzzy-based aggregation method has been introduced in [5]. The results showed that the proposed fuzzy decisioning method improves the performance of BEECLUST especially in the presence of noise.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, utilizing continuous and long-term of the chemical pheromones in the laboratory environment would be harmful. Therefore, artificial media such as RFID [9], audio [10]- [12] and light [5], [13]- [15] could be the safe media to be used as the artificial pheromone and cue. Garnier et al [16] presented an experimental setup for study on pheromone based communication with micro autonomous robots using the projected light.…”
mentioning
confidence: 99%